DINAMIKA KEPEMIMPINAN DALAM TIM MANAJEMEN PUNCAK: IMPLIKASI TERHADAP PENGAMBILAN KEPUTUSAN STRATEGIS PADA BANK-BANK DI INDONESIA - Ismi Avissa, Nadia; Mustofa, Amirul; Yunus, Eddy (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the leadership dynamics within Top Management Teams (TMT) and their influence on strategic decision-making in Indonesian banks. The research adopts a qualitative descriptive approach, collecting data through document analysis and indirect interviews. The results indicate that diversity within TMT, in terms of educational background, experience, and gender, positively influences the quality and innovation of strategic decisions. This diversity allows TMT to develop decisions that are more adaptive to external changes, such as technological advancements and regulatory changes. However, challenges arise in the decision-making process, particularly regarding difficulties in reaching consensus among TMT members. The power dynamics within TMT, whether centralized or distributed, also play an important role in strategic decision-making. These findings provide important insights for Indonesian banks to strengthen internal collaboration and diversity to create more innovative and adaptive strategic decisions in the future.